Sustainable Entrepreneurship Development Training for Sindangheula Community in Utilizing Village Potential - Ikhwan, Afiful; Pertiwi, Widya Nur Bhakti; Gunawan, Nuri Atikah; Hudiafa, Eva; Jannah, Shohifatul (EQUATOR SINAR AKADEMIA, 2024)
Sindangheula Village is one of the villages in Indonesia that has great local economic potential, especially as a center for producing broomsticks. However, although broomstick production in Sindangheula Village has great market potential, business management and development still face various challenges, especially in terms of product innovation, business management, and effective marketing strategies. Based on these potentials and challenges, this study aims to measure the extent to which this training has an impact on improving the economic and social welfare of the village community. The community service method used in sustainable entrepreneurship training in Sindangheula Village consists of initial observation, theory and practice training, business mentoring, and evaluation. The implementation of the community service program in the form of sustainable entrepreneurship training for the Sindangheula Village community has had a positive impact, namely increasing community understanding of entrepreneurship, technical skills, product innovation, and digital marketing strategies. With the formation of business groups, collaboration occurs between community members in the production process, distribution, and product marketing.